KONFLIK DALAM KOMUNIKASI POLITIK ANTARA LEGISLATIF DAN EKSEKUTIF DALAM MENYIKAPI RENCANA RTRW DI KABUPATEN BULUKUMBA - Haris, Syahruni; Cangara, Hafied (KAREBA : Jurnal Ilmu Komunikasi, 2014)
Abstract Executive policy-related polemics often leads to war of opinion that led to a conflict with the legislature, one of which is the formulation of the Draft Regulation (Ranperda) on Spatial Planning (Spatial) Bulukumba. This study aims to determine the pattern of the relationship between the executive and legislative communications along with constraints and problems encountered in the implementation of the authority and form of the conflict between the executive and the legislature in lawmaking Spatial Bulukumba. The method used is qualitative approach. Data obtained directly by using interviews with informants about the conflict in political communication in addressing regional legislative policy as the executive regent Bulukumba on Spatial Ranperda Bulukumba. The data in this study using the model data analysis komponensial (componential anaylisis). The results showed that the pattern of the relationship between the executive and legislative communication in conflict resolution in the determination of Bulukumba Spatial regulation is through the process of formal organizational communication and informal organizational communication. Form of the conflict between the executive and the legislature in lawmaking Spatial Bulukumba is a conflict between organizations, between the executive and legislative Bulukumba. Obstacles encountered in the implementation of the authority in improving the working relationship between the executive and legislative include confusion of data as outlined in the draft executive Academic legislative Spatial and lack of understanding of the spatial plan so that no critical response from the legislature in this formulation. While efforts to improve the working relationship between the executive and the legislature is to override individual interests and the public interest.Abstrak Berbagai polemik terkait kebijakan eksekutif sering berujung pada perang opini dengan legislatif yang berujung koflik, salah satunya adalah dalam perumusan Rancangan Peraturan Daerah (Ranperda) tentang Rencana Tata Ruang Wilayah (RTRW) Kabupaten Bulukumba. Penelitian ini bertujuan untuk mengetahui pola hubungan komunikasi antara eksekutif dan legislatif beserta kendala dan masalah yang dihadapi dalam pelaksanaan kewenangan dan bentuk konflik yang terjadi antara eksekutif dan legislatif dalam penyusunan Perda RTRW Kabupaten Bulukumba. Metode yang digunakan yaitu pendekatan kualitatif. Data yang diperoleh secara langsung dengan menggunakan wawancara terhadap informan tentang konflik dalam komunikasi politik legislatif daerah dalam menyikapi kebijakan Bupati Bulukumba selaku eksekutif tentang Ranperda RTRW Kabupaten Bulukumba. Data dalam penelitian ini menggunakan analisis data model komponensial (componential anaylisis). Hasil penelitian menunjukkan bahwa pola hubungan komunikasi antara eksekutif dan legislatif dalam penyelesaian konflik dalam penetapan Perda RTRW Kabupaten Bulukumba yaitu melalui proses komunikasi organisasi formal dan komunikasi organisasi informal. Bentuk konflik yang terjadi antara eksekutif dan legislatif dalam penyusunan Perda RTRW Kabupaten Bulukumba adalah konflik antarorganisasi, yakni antara lembaga eksekutif dan legislatif Kabupaten Bulukumba. Kendala yang dihadapi dalam pelaksanaan kewenangan dalam meningkatkan hubungan kerja antara eksekutif dan legislatif diantaranya adalah kerancuan data yang dituangkan eksekutif dalam draft Naskah Akademis RTRW dan kurangnya pemahaman legislatif terhadap RTRW sehingga tidak ada tanggapan kritis dari legislatif dalam perumusan ini. Sedangkan upaya untuk meningkatkan hubungan kerja antara eksekutif dan legislatif yaitu dengan mengesampingkan kepentingan-kepentingan individual dan mengutamakan kepentingan masyarakat.Â